Different Resistance-Training Regimens Evoked a Similar Increase in Myostatin Inhibitors Expression - Santos, A. R.; Lamas, L.; Ugrinowitsch, C.; Tricoli, V.; Miyabara, E. H.; Soares, A. G.; Aoki, M. S. (International Journal of Sports Medicine, 2015)
The aim of the present study was to investigate the effect of different resistance-training regimens (S or P) on the expression of genes related to the MSTN signaling pathway in physically-active men. 29 male subjects with at least 2 years of experience in strength training were assigned to either a strength-training group (S; n=11) or a power-training group (P; n=11). The control group (C; n=7) was composed of healthy physically-active males. The S and the P groups performed high- and low-intensity squats, respectively, 3 times per week, for 8 weeks. Muscle biopsies from the vastus lateralis muscle were collected before and after the training period. No change was observed in MSTN, ACTIIB, GASP-1 and FOXO-3 A gene expression after the training period. A similar increase in the gene expression of the inhibitory proteins of the MSTN signaling pathway, FLST (S: 4.2 fold induction and P: 3.7 fold induction, p<0.01) and FL-3 (S: 5.6 fold induction and P: 5.6 fold induction, p<0.01), was detected after the training period. SMAD-7 gene expression was similarly augmented after both training protocols (S: 2.5 fold induction; P: 2.8 fold induction; p<0.05). In conclusion, the resistance-training regimens (S and P) activated the expression of inhibitors of the MSTN signaling pathway in a similar manner.
Keywords: strength training; power training; gene expression; real time PCR